2010
DOI: 10.1007/s12033-010-9348-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Factors Affecting the Accumulation of Recombinant Proteins in the Chlamydomonas reinhardtii Chloroplast

Abstract: In an effort to develop microalgae as a robust system for the production of valuable proteins, we analyzed some of the factors affecting recombinant protein expression in the chloroplast of the green alga Chlamydomonas reinhardtii. We monitored mRNA accumulation, protein synthesis, and protein turnover for three codon-optimized transgenes including GFP, bacterial luciferase, and a large single chain antibody. GFP and luciferase proteins were quite stable, while the antibody was less so. Measurements of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…In some cases, expression levels can be improved by using the stronger promoter from the gene for the 16S ribosomal RNA fused to the 5¢UTR of a photosynthetic gene [27,61]. However, more often it is the performance of the 5¢UTR that is the bottleneck [62], with the efficiency of translation constrained by either the same feedback regulation that prevents the over-accumulation of individual photosynthetic subunits in the absence of their assembly partners (so-called 'control by epistasy of synthesis'), or by competition with the corresponding endogenous gene transcript for trans-acting factors that are required for transcript stability or translation, but are present in limiting concentration in the chloroplast [63]. The strategies to overcome this involve either replacement of the 5¢UTR of the endogenous gene with that from another photosynthetic gene [64] or, more elegantly, the development of synthetic variants of the 5¢UTR that are no longer subject to these limitations and therefore enable improved expression of the transgene [65].…”
Section: Emerging Synthetic Biology Approachesmentioning
confidence: 99%
“…In some cases, expression levels can be improved by using the stronger promoter from the gene for the 16S ribosomal RNA fused to the 5¢UTR of a photosynthetic gene [27,61]. However, more often it is the performance of the 5¢UTR that is the bottleneck [62], with the efficiency of translation constrained by either the same feedback regulation that prevents the over-accumulation of individual photosynthetic subunits in the absence of their assembly partners (so-called 'control by epistasy of synthesis'), or by competition with the corresponding endogenous gene transcript for trans-acting factors that are required for transcript stability or translation, but are present in limiting concentration in the chloroplast [63]. The strategies to overcome this involve either replacement of the 5¢UTR of the endogenous gene with that from another photosynthetic gene [64] or, more elegantly, the development of synthetic variants of the 5¢UTR that are no longer subject to these limitations and therefore enable improved expression of the transgene [65].…”
Section: Emerging Synthetic Biology Approachesmentioning
confidence: 99%
“…In their preponderance, these entail heterologous transformation of microalgal chloroplasts as a synthetic biology platform for the production of biopharmaceutical and therapeutic proteins (Dyo and Purton, 2018, and references therein). The vast majority of such efforts have employed transformation of the chloroplast in the model green microalga Chlamydomonas reinhardtii via double homologous recombination of exogenous constructs encoding heterologous proteins (Demain and Vaishna, 2009;Surzycki et al, 2009;Tran et al, 2009;Coragliotti et al, 2011;Gregory et al, 2013;Jones and Mayfield, 2013;Rasala and Mayfield, 2015;Baier et al, 2018). A common feature of these efforts is the low yield of the transgenic proteins, rarely exceeding 1% of the total Chlamydomonas reinhardtii protein (Dyo and Purton, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The final optimized sequences in the present study demonstrated the values consistent with the aforementioned range. The wild-type genes containing low frequent codons will result in low translation efficiency or even disengaging the translational machinery (41). In the present study the low frequent codons (<30%) were modified as much as possible.…”
Section: Gene Optimizationmentioning
confidence: 85%
“…It has been proven that, the recognition of start codon (AUG) by ribosomes in eukaryote mRNAs can be influenced by its flanking sequences (21). Hence, the less disturbance (secondary structures) near the main AUG codon particularly in its preceding 14 nucleotides, the better facilitation in the recognition procedure and consequently the more efficient translation (65,41). Several experimental evidences are available showing the critical role of (A/G) -3 in translation initiation enhancement (66,67).…”
Section: Translation Initiation Site (Tis)mentioning
confidence: 99%